Implementation of Metallic Vertical Interconnect Access in Hybrid Intercalated Graphene/Quantum Dot Photodetector for Improved Charge Collection - Chen, Wenjun; Ahn, Seungbae; Rangel, Carlos; Vazquez-Mena, Oscar (Frontiers in Materials, 2019)
Colloidal quantum dots (QDs) are of great interest in optoelectronic and photovoltaic devices with low-cost processing, strong light absorption, and size tunable direct band gap. However, their limited carrier mobility and short diffusion length limit efficient charge collection and transport. The short diffusion length in QD solid films, 100–200 nm, limits their thickness to t≈200–300 nm, resulting in poor absorption in the near-infrared, lambda>800 nm, wasting part of sunlight and reducing power conversion efficiency. Recently, a novel architecture based on multiple graphene monolayers (Gr) intercalated inside QD films was reported to improve charge extraction beyond QDs diffusion length. The intercalated graphene layers ensure efficient charge collected in QD films thicker than the diffusion length. However, this architecture still fails to collect carriers from the QDs when the thickness is >200 nm due to the poor vertical conductivity of the devices. Herein, we present the fabrication, optimization and implementation of intercalated devices with vertical interconnecting contacts, increasing carrier collection and photocurrent, aiming to develop a novel architecture for improved photodetection and photovoltaics with QDs. First, we analyze the individual roles of Gr and QDs, studying the evolution of light absorption, photocurrent, and conductivity as successive QD and Gr layers are added. We find the optimal interspacing between graphene layers in the intercalated system, aiming for the best compromise between light absorption and efficient charge collection. Our main contribution is the implementation of vertical interconnect access (VIAs) to each graphene layer to ensuring efficient charge transfer from Gr to the gold electrical contacts for efficient current collection. We show that for 850 nm wavelength illumination, photocurrent of intercalated devices show a 10 fold improvement over devices without VIAs. We also use a back-gate voltage to monitor Fermi level shift in Gr and charge transfer from QDs to Gr. The intercalated configuration with VIAs contacts herein presented is a significant improvement in charge collection for QD optoelectronic applications as well as a promising architecture to enhance the power conversion efficiency for QD solar cells.